Forecasting the Number of Tuberculosis Patients Using Automatic Clustering And Fuzzy Logical Relationship Method - Rahmawati, Rahmawati; Sarbaini, Sarbaini; Rahma, Ade Novia; Lestari, Tri Uci; Aryani, Fitri (CAUCHY: Jurnal Matematika Murni dan Aplikasi, 2023)
Tuberculosis is an infectious disease caused by the bacterium Mycobacterium tuberculosis bacillus, which infects the lungs and can potentially cause death.  This study aims to predict the number of tuberculosis sufferers in Kampar Regency in 2022. The method used is the automatic clustering and fuzzy logical relationship method. The data analyzed is secondary data obtained from the Kampar District Health Office from 2017 to 2021. From the results of the analysis carried out using the automatic clustering and fuzzy logical relationship method, it was obtained to forecast the number of tuberculosis patients in 2022, as many as  944 people with MAPE of 0.0882%, the accuracy of forecasting results of 99.9118%, and an increase in the number of tuberculosis sufferers from 2021 to 2022 as many as 4 people.